Climate-Based Management Options for North Central Florida Beef Cattle Producers - Norman Breuer; Victor Cabrera; Peter E. Hildebrand; James W. Jones (EDIS)
The objective of this study was first to understand how ENSO seasonal change interacts with grass production and cow-calf production in north central Florida, and second, what management decisions ranchers could make to reduce risk and vulnerability, thus taking advantage of improved forecasts. For this study, 38 ranchers and 41 extension agents were interviewed. This document is Circular 1476, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published May 2005.